Use of CAMEL rating framework: a comparative performance evaluation of selected Bangladeshi public, private and foreign commercial banks - Fatema, Mossammot Kaniz (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.